Case Report: Whole-Exome Sequencing of Hypothalamic Hamartoma From an Infant With Pallister-Hall Syndrome Revealed Novel de novo Mutation in the GLI3 - Yang, Yue; Shen, Fang; Jing, Xie-Pan; Zhang, Nu; Xu, Shang-Yu; Li, Dan-Dong; Zhou, Ling-Li; Bai, Guang-Hui; Fang, Huang-Yi; Zhang, Zhong-Ding; Pang, Chen; Lin, Jian; et al. (Frontiers in Surgery, 2021)
Background: GLI-Kruppel family member 3 (GLI3), a zinc finger transcription factor of the sonic hedgehog pathway, is essential for organ development. Mutations in GLI3 cause several congenital conditions, including Pallister-Hall syndrome (PHS), which is characterized by polydactyly and hypothalamic hamartoma. Most patients are diagnosed soon after birth, and surgical removal of hypothalamic hamartoma in the very young is rarely performed because of associated risks. Case presentation: A 7-month-old boy with PHS features, including a suprasellar lesion, biﬁd epiglottis, tracheal diverticulum, laryngomalacia, left-handed polydactyly and syndactyly, and omental hernia was referred to our service. His suprasellar lesion was partially removed, and whole-exome sequencing was applied to the resected tumor, his peripheral blood, and blood from his parents. Histopathology confirmed the diagnosis of hypothalamic hamartoma, and molecular profiling revealed a likely pathogenic de novo variant, c.2331C>G (p. H777Q), in GLI3. Magnetic resonance imaging follow-up 1 year later showed some residual tumor, and the patient experienced normal development post operation. Conclusions: We presented a case of PHS that carries a novel GLI3 variant. Hypothalamic hamartoma showed a distinct genetic landscape from germline DNA. These data offer insights into the underlying etiology of hypothalamic hamartoma development in patients with PHS.